Determination of Interest Rate in Nepalese Finance Companies (Management Dynamics, 2020)
Finance companies are the institutions that are incorporated under company act to perform non-bankingactivities arrangements and operation of different schemes. The finance companies survive by makingprofit which is the interest spread i.e. difference between interest received and interest charged. Themain aim of this paper was to determine the responsible factors for the interest rate determinationof Nepalese financial companies. The factors affecting interest rate charged and offered by Nepalesefinancial companies are analyzed using Regression Analysis. Out of the total financial companies onlytwo ICFC Finance Company and United Finance Company are taken as samples. Secondary data arecollected from various publications, websites, and annual reports. Interest rate on deposit of ICFCFinance has significant negative association with inflation rate and significant positive relation withinterest rate on loan and advance of the company. Similarly, interest rate on loan and advance of thecompany has significant positive relation with interest rate on deposit and interest rate on loan andadvance also has positive relation with inflation rate. Interest rate on deposit of United Finance hassignificant negative association with inflation rate and significant positive relation with interest rateon loan and advance of the company. Similarly, interest rate on loan and advance of the company hassignificant positive relation with both interest rate on deposit and inflation rate.